Lange Practice Tests for the USMLE Step 1 (Lange's Practice Tests for the USMLE Step 1) - Goldberg Joel S (MC Graw Hill, 2006)
This resource features thirteen comprehensive practice tests with a total of 650 questions along with many new clinical vignette style questions.